Hybridism in the understanding of media “stories”: An analysis of the Romanian popularity of K-dramas1 - Marinescu, Valentina (Academic Quarter | Akademisk kvarter, 2011)
Valentina Marinescu’s Hybridism in the understanding of media "stories" - An analysis of the Romanian popularity of K-drama treats a very recent phenomenon in Romania: the nation-wide exposure to "Hallyru" popular culture products. The article aims at explaining the reasons of the popularity of this type of products with the Romanian viewers, and to give an answer to how Korean historical drama series viewing influence Romanians’ perceptions in general and especially their perceptions of Asia.